Análise crítica da necessidade de utilização de pessoal externo para consolidação do programa de auditorias de um organismo de acreditação - Fonseca, Heliane (2004)
This work aims to seeking the evolutive memory of the accreditation program from Brazilian Bodies, to raise a discussion about the no planned growing issue and its related problems in the accreditation operational sector of System Certification Bodies, Sesit, of Cgcre/Inmetro. In this sense, it reviews the use of external personnel to consolidate the audit program, so as to meet the several sectorial needs and the growing accreditation demand